FACTORS INFLUENCING THE FUTURE OF CULTURAL TOURISM - Popova, Daniela (E-Journal VFU, 2025)
Cultural tourism has a vision to advertise, promote and provide new directions for the development of the economy. The factors that influence its future are related with the preservation and protection of cultural heritage on the hand, and on the other – with creativity, craft achievements, innovations in tourism management and aestheticization as a form of environment that is constantly being improved. The aim of the paper is to present the relationship between the factors affecting cultural tourism and its future development.
Keywords: culture; tourism; development